The blockchain DAO as an evolution of the North American trust: Legal and philosophical aspects - Rivero-Silva, Sebastián (DICERE Revista de Derecho y Estudios Internacionales, 2025)
This article explores the philosophical foundations of the North American trust and its connection to blockchain technology, proposing that Decentralized Autonomous Organizations (DAOs) represent its direct technological evolution. Rooted in Common Law traditions, the trust derives from an emphasis on negative liberty, where individuals shield their property from state intervention by transferring legal ownership to a trustee. This arrangement maintains autonomy and resists potential shifts in government regulation or policy. DAOs, driven by self-executing smart contracts, retain the trust’s fundamental purpose—protecting assets and ensuring independent governance—while eliminating reliance on a single fiduciary. By dispersing administrative power across a decentralized network, DAOs enhance resilience against political and economic unpredictability. However, European jurisdictions, influenced by Rousseau’s notion of positive liberty, traditionally subordinate property to the collective interest, thus restricting trusts and, more recently, imposing regulatory measures on blockchain organizations. In Europe, this idea often collides with legal frameworks that prioritize public interests, leading to regulatory scrutiny of blockchain-based systems. Despite these challenges, DAOs continue to refine the trust’s core principles in a technologically advanced environment, offering security and autonomy. Ultimately, this evolution reaffirms the enduring tension between individual freedom from governmental authority that underpins the Anglo-Saxon legal tradition.